Reflections of the 'export-led growth' or 'growth-led exports' hypothesis on the Turkish economy in the 1999-2021 period - Ayhan Orhan; Melek Emikönel; Murat Emikönel; Rui Alexandre Castanho (Economies, 2022)
Various factors determine and affect economic growth, one of which is exports. Trade theory also states that exports increase the growth of the domestic economy in various ways. For this reason, the effect of exports on economic growth is a long-term area of research. In addition to the studies examining the effect of foreign trade on economic growth in the literature, some studies investigate the effects of economic growth on export capacity. These studies suggest that the export-based economic growth hypothesis is valid when the causality relationship between exports and growth is from exports to growth, and the growth-led export hypothesis is valid when it is from growth to exports. To this end, the primary purpose of this study is to investigate the validity of the new economic model for Turkey in two different periods. In this context, this study comparatively focuses on the 1999:Q1-2013:Q4 and 2014:Q1-2021:Q4 periods to test the validity of the export-led growth hypothesis and the growth-led export hypothesis. According to the analysis results for the 1999:Q1-2013:Q4 periods, only the growth-led export hypothesis is valid, and a 1% increase in the economic growth rate in this period increases exports by 0.42%. Considering the 2014:Q1-2021:Q4 period, the hypotheses of 'Economic growth is not the cause of exports and exports are not the cause of economic growth' are rejected, and according to these test results, it was determined that both the export-led growth hypothesis and the growth-led export hypothesis are valid. In the results of this period, a 1% increase in economic growth rate increases exports by 0.38%, and a 1% increase in exports increases economic growth by 1.36%.
Keywords: 330; causality; export-led growth; growth-led export; new economic model